2017
DOI: 10.1371/journal.pone.0184826
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of norovirus among children with diarrhea in four major hospitals in Bhutan: Replacement of GII.21 by GII.3 as a dominant genotype

Abstract: BackgroundDiarrhea is a major cause of morbidity and mortality among Bhutanese children. The etiology of diarrhea is not well known due to the challenges of conducting routine surveillance with Bhutan’s modest research facilities. Establishing an etiology is crucial toward generating evidence that will contribute to policy discussions on a diarrheal disease control program. Our previous study, during 2010–2012, revealed that norovirus (NoV) is an important cause of diarrhea among Bhutanese children, and that G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
4
12
0
Order By: Relevance
“…The amplicon size of the partial RdRp gene is 470 bp. The RT-PCR results were confirmed by nucleotide sequencing of the amplicons 5 . The nucleotide sequence of the amplicons was determined by the BigDye Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems, Foster City, CA) according to the manufacturer's instructions and the product was run on a ABI Prism 3100 Genetic Analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 74%
“…The amplicon size of the partial RdRp gene is 470 bp. The RT-PCR results were confirmed by nucleotide sequencing of the amplicons 5 . The nucleotide sequence of the amplicons was determined by the BigDye Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems, Foster City, CA) according to the manufacturer's instructions and the product was run on a ABI Prism 3100 Genetic Analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 74%
“…The oldest GII.3 NV strain identified to date is from a 1983 sample isolated in the Goulburn Valley of Australia [13], and GII.3 has been reported to be the major cause of sporadic pediatric NV infection [15,17,35,36]. In China, early reports on NV showed GII.3 was prevalent in 1999 [37,38], and until now, GII.3 was reported as the dominant genotype next to GII.4 in sporadic NV infection [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the large number of NV genotypes cocirculating in children over the past decade, genotypes GII.4 and GII.3 have predominated worldwide [13][14][15][16][17]. Up to nowadays, six outbreaks of acute gastroenteritis are associated with at least seven distinct GII.4 NV variants [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GI and GII viruses are frequently detected in humans, and are further classified into 9 and 27 genotypes, respectively, based on the capsid region sequences (Chhabra et al, 2019). Previous molecular epidemiological studies have shown that some NoV GII genotypes, including GII.2,GII.3,GII.4,GII.6,and GII.17 are prevalent in different countries (Matsushima et al, 2015;Bruggink et al, , 2018Cannon et al, 2017;Wangchuk et al, 2017).…”
Section: Introductionmentioning
confidence: 99%